The Skeletal and Soft Tissue Facial Profile in Adolescent and Adult - Saba H Al-Zubaidi (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate the norms for several cephalometric soft tissue measurements and to investigatedifferences in the mean values of these measurement between two age groups (11-14 and 18-25) andbetween two gender. Materials and Methods: The adolescent sample consists from 30 subjects (15 foreach gender) with age range from 11 -14 years. The adult sample consists from 30 subjects (15 foreach gender) with age range 18-25 years. The two groups satisfying the criteria of balance facial profile,class I molar relation ship and normal over bite-over jet relation ship. Ten skeletal and soft tissuemeasurements were obtained from tracing lateral cephalometric radiograph. The data was analyzedusing descriptive statistic and student t- test. Results: During adolescence, no significant differenceswere found between males and females. During adulthood, the males having higher values for all measurements(except nasolabial and mentolabial angles) but statistically not significant. From adolescentto adult males, the angles of facial convexity, Z- angle in addition to lower lip length and nasal depthare significantly different with the adult male having the higher value. For females, the lower lip lengthand nasal depth significantly higher in the adult period. Conclusions: The adult males having relativelystraighter facial profile. In addition, Z- angle also greater in the adult males than during adolescence.For both genders, the nasal depth and the vertical height of lower lip were significantly greater inadults.